Hypersaline Microbial Self-Powered Biosensor with Increased Sensitivity. Issue 5 (11th April 2018) - Grattieri, Matteo; Hickey, David P.; Alkotaini, Bassam; Robertson, Stuart J.; Minteer, Shelley D.
Abstract : The on-line, self-powered monitoring of the organic carbon content in hypersaline solutions (e.g. chemical oxygen demand, COD) based on a microbial biosensor would avoid the generation of toxic waste, originated by common COD analytical methods, and reduce the release of pollutants into the environment. Herein, a disposable cathode was applied to microbial fuel cells (MFCs) for the environmental friendly monitoring of the COD reaching a sensitivity one order of magnitude higher compared to the MFC with an air breathing cathode. Additionally, the entrapment of bacterial cells in alginate-capsules ensured a considerable linear range (up to approximately 10, 000 mg COD L −1 ), providing opportunities for the wide application of the device to hypersaline solutions characterized by different origins and contamination levels.